Temporary employee and Company Social Benefits Fund of the employer-user and equal treatment in employment – de lege ferenda remarks - Bigaj, Wojciech (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The author analyses the current legal status concerning the possibility for temporary employees to use the Company Social Benefits Fund in cases where such a fund has been created by the employer-user. It also presents the practice of employer-users in this field and proposes legislative changes to increase the level of equal treatment of employees and temporary workers providing work for the same employer.